Process for producing dienes

JP7627694B2Active Publication Date: 2025-02-06VERSALIS SPA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022529934
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-20
Filing Date
2020-12-18
Publication Date
2025-02-06
Estimated Expiration
2040-12-18

Smart Images

  • Figure 0007627694000001
    Figure 0007627694000001
  • Figure 0007627694000002
    Figure 0007627694000002
  • Figure 0007627694000003
    Figure 0007627694000003
Patent Text Reader

Abstract

1. A process for producing a diene, preferably a conjugated diene, more preferably 1,3-butadiene, comprising dehydrating at least one alkenol in the presence of at least one acid catalyst based on silica (SiO) and alumina (AlO), preferably at least one catalytic material comprising silica-alumina (SiO-AlO), wherein the catalyst has an alumina content (AlO) of 12 wt. % or less, preferably 0.1 wt. % to 10 wt. % based on the total weight of the catalyst (the alumina content refers to the total weight of the catalyst without binder), and a pore mode diameter of 9 nm to 170 nm, preferably 10 nm to 150 nm, even more preferably 12 nm to 120 nm. Preferably, the alkenol can be obtained directly from a biosynthetic process or by catalytic dehydration of at least one diol, preferably butanediol, more preferably 1,3-butanediol, even more preferably bio-1,3-butanediol derived from a biosynthetic process. Preferably, the 1,3-butadiene is bio-1,3-butadiene.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a process for producing dienes.

[0002] More specifically, the present invention relates to a process for producing dienes, preferably conjugated dienes, more preferably 1,3-butadiene, comprising the dehydration of at least one alkenol in the presence of at least one catalytic material comprising at least one acid catalyst based on silica (SiO) and alumina (AlO), preferably silica-alumina (SiO-AlO), said catalyst having a specific alumina content (AlO) and specific pore characteristics, in particular a specific pore mode diameter.

[0003] Preferably, said alkenol can be obtained directly from a biosynthetic process or by a catalytic dehydration process of at least one diol, preferably butanediol, more preferably 1,3-butanediol, even more preferably bio-1,3-butanediol derived from a biosynthetic process. Preferably, said 1,3-butadiene is bio-1,3-butadiene.

[0004] The industrial production of 1,3-butanediol, 1,3-butadiene and alkenols is currently known to be based on classical petrochemical processes.

[0005] In fact, diols generally having four carbon atoms, and in particular 1,3-butanediol (also commonly referred to as 1,3-BDO), are usually obtained by complex petrochemical processes, as described, for example, in Grafje H. et al., "Butanediols, Butenediol, and Butynediol", "Ulmann's Encyclopedia of Industrial Chemistry" (2000). In particular, 1,3-butanediol is produced via acetaldehyde, hydroxybutyraldehyde and subsequent reduction, and is generally used as a resin component or solvent.

[0006] Processes for producing alkenols are also known in the art.

[0007] For example, US Patent No. 5,406,007 describes a process for producing allyl alcohol, homoallylic alcohol or a mixture thereof, which comprises hydrogenating an epoxyalkene having an ethylenic unsaturation conjugated with an epoxy group in the presence of a sulfur or sulfide modified nickel catalyst, operating under conditions of temperature and pressure typical of hydrogenation.Preferably, the process is useful for preparing a mixture of 2-buten-1-ol (crotyl alcohol) and 3-buten-1-ol.

[0008] U.S. Pat. No. 6,278,031 describes a compound of formula (I): H2R 1 -R 2 C=CR 3 -CR 4 R 5 -OR 6 (I) A process is described for preparing a 2-buten-1-ol compound having the formula: In the formula, the group R 1 , R 2 , R 3 , R 4 , R 5 and R 6 are each independently hydrogen or an aliphatic group optionally substituted with an OH or OR group, R is an aliphatic group, a halogen, or a carboxyl group, and R 2 represents a -CHO group, or R 2 and R 5 form an alicyclic ring together with the carbon atom located between them, and R 6 is a cycloaliphatic, araliphatic, aromatic group or -C(=O)-R 7 represents a group, R 7 is an aliphatic, cycloaliphatic, araliphatic or aromatic group, and the process comprises reacting a compound represented by formula (II) HR 1 C=CR 2 -CHR3 -CR 4 R 5 -OR 6 (II) isomerizing a 3-buten-1-ol compound having the formula In the formula, the group R 1 , R 2 , R 3 , R 4 , R 5 and R 6 has the same meaning as above, and in the presence of hydrogen and a catalyst, the process is carried out continuously on a fixed bed catalyst, the catalyst comprising palladium and selenium or tellurium or a mixture of selenium and tellurium on a silicon dioxide support, 80 m 2 / g~380m 2 0.6 cm2 with a BET surface area of ​​0.6 cm3 / g and a pore diameter of 3 nm to 300 nm 3 / g~0.95cm 3 / g, and 80% to 95% of the pore volume have a pore diameter of 10 nm to 100 nm.

[0009] Alternatively, 2-buten-1-ol (crotyl alcohol) can be prepared by reducing crotonaldehyde, for example, as described in the "Merck Index" (1976), 9th edition. Furthermore, 2-buten-1-ol (crotyl alcohol) can be prepared by biosynthetic processes, for example, as described in WO 2013 / 130481 (as an intermediate in the synthesis of 1,3-butadiene) or U.S. Patent Application No. 2013 / 109064.

[0010] U.S. Pat. No. 4,400,562 describes a method for synthesizing alkenols from 1,3-butanediol in a liquid phase, which includes mixing a catalyst, a sulfate of a trivalent metal selected from aluminum sulfate, chromium sulfate, iron sulfate, and a mixture thereof, with an effective amount of 1,3-butanediol, obtaining a mixture of the catalyst suspended in 1,3-butanediol, heating the mixture to a temperature about 70° C. lower to about 100° C. higher than the boiling point of 1,3-butanediol to perform a partial dehydration reaction of 1,3-butanediol and obtain 3-buten-1-ol that evaporates from the reaction mixture, and condensing the vapor to isolate 3-buten-1-ol.

[0011] Alternatively, 3-buten-1-ol can be prepared from propylene and formaldehyde, operating at high temperatures using a catalyst, as described, for example, in US Patent Application No. 2013 / 109064.

[0012] 3-Buten-2-ol (methyl vinyl carbinol) and butadiene can be obtained, for example, by dehydration of 2,3-butanediol using thorium oxide, as described in Winfield ME, “The catalytic Dehydration of 2,3-butanediol to Butadiene. II. Adsorption Equilibria”, “Australian Journal of Scientific Research” (1950), Vol. 3(2), pages 290-305.

[0013] Alternatively, 3-buten-2-ol (methyl vinyl carbinol), alone or in mixtures with other butenols, can be obtained by pyrolysis of polyols or their derivatives (e.g. 1,3-butylene glycol diacetate), as described, for example, in German Patent No. 1,150,671, or by reduction of acetylene or unsaturated carbonyl compounds, as described, for example, in Russian Patent No. 396312 or Japanese Patent Application No. 63 / 222135.

[0014] 2-Buten-1-ol (crotyl alcohol) can be used, for example, as a precursor for halides, crotyl esters or crotyl ethers, which can be used, for example, as intermediates in the production of monomers, in fine chemistry (e.g. for the production of sorbic acid, trimethylhydroquinone, crotonic acid, 3-methoxybutanol), agricultural chemistry, pharmaceutical chemistry.

[0015] 3-Buten-1-ol (allyl carbinol) can be used, for example, in medicinal chemistry, agricultural chemistry, perfume, and resin raw materials. For example, the coupling reaction of 3-buten-1-ol (allyl carbinol) with aryl halides catalyzed by palladium gives aryl-substituted aldehydes, which can be used, for example, as anxiolytics in medicinal chemistry.

[0016] 3-Buten-2-ol (methylvinylcarbinol) can be used as a solvent, in fine chemistry, for example as a component in the modification of polymers such as polyolefins (as described, for example, in German Patent No. 1,908,620).

[0017] The alkenols may also be used to produce 1,3-butadiene.

[0018] 1,3-butadiene is a major petrochemical product. Approximately 10 million tons of 1,3-butadiene are produced annually and are preferably used to manufacture various products such as synthetic rubber, resins, acrylonitrile-butadiene-styrene terpolymers (ABS), hexamethylenediamine, butanediol, especially 1,4-butanediol. More than 95% of the 1,3-butadiene produced annually is a by-product from the steam cracking process for producing ethylene and other olefins and is separated by extractive distillation. Specific processes for producing 1,3-butadiene include, for example, the dehydrogenation of butane and / or butene.

[0019] The possibility of developing alternative, efficient and manufacturable processes for 1,3-butadiene with reduced production costs and environmental impact remains of great interest. In particular, novel processes that can use materials derived from biosynthetic processes, such as bioalkenols, especially those derived from catalytic dehydration of bio-1,3-butanediol, to produce bio-1,3-butadiene by further catalytic dehydration, are of great interest.

[0020] The carbon source in the biosynthetic process may be from renewable sources, biomass, syngas or other gaseous carbon sources.

[0021] Syngas can be obtained by gasification of carbon-containing materials (eg, coal, biomass, waste, natural gas, etc.) through processes known in the art.

[0022] The biosynthetic process is generally carried out via a microorganism capable of utilizing a carbon source, such as, for example, carbohydrates, such as sugars (glucose, xylose, arabinose, fructose, etc.), biomass (cellulosic, hemicellulosic, lignin, etc.), preferably carbohydrate-containing, or other renewable resources.

[0023] The production of 1,3-butadiene from diols is known in the art, but the processes that have found industrial application, even in specific and / or unconventional situations, are based on the Reppe-type technology using phosphate-based catalysts, see in this regard the article by Bender M., “An Overview of Industrial Processes for the Production of Olefins - C4 Hydrocarbons”, “ChemBioEng Reviews” (2014), Vol. 1. No. 4, pages 136-147 (DOI:10.1002 / cben.201400016). However, said processes are not considered industrially feasible today due to the low productivity, the specific reaction conditions used and the fast decay of the catalysts used, as can be seen, for example, from the literature reported below.

[0024] US Patent 2,310,809 describes a process for producing diolefins, in particular 1,3-butadiene, by catalytic dehydration of aliphatic glycols having at least 4 carbon atoms, which comprises contacting said glycols in the form of vapor, preferably steam or another diluent gas, with a dehydration catalyst selected from phosphorus-containing compounds capable of operating at high temperatures. The process is said to increase the yield of diolefins, reduce the formation of by-products, and maintain a long catalyst life (in particular, Examples 1 and 2 show that the yield of 1,3-butadiene starting from 1,3-butanediol is equivalent to 85% and 90%, respectively). However, the aforementioned process requires very low feed rates (Example 1 shows 0.060 kg x h in the presence of n-hexane). -1 xl -1 , equivalent to 60 parts of 1,3-butanediol and 40 parts of water; in Example 2, together with tetrahydrofuran, 0.060 kg x h -1 xl -1The catalyst is difficult to manufacture due to the use of a mixture of 40 parts of 1,3-butanediol, 40 parts of water, and 20 parts of 1,4-butanediol. In addition, to improve the stability of the catalyst, organic substances that are liquid under normal conditions, such as n-hexane, are vaporized on the catalyst.

[0025] U.S. Pat. No. 2,237,866 describes a process for producing diolefins, in particular 1,3-butadiene, through the catalytic dehydration of the corresponding glycols and alcohols in the vapor phase in the presence of a catalyst selected from phosphorus-containing substances (e.g., phosphorus-containing acid esters, phosphorus oxychloride, phosphorus trichloride, phosphorus pentachloride).

[0026] US Pat. No. 2,426,678 describes a method for regenerating a dehydration catalyst based on a phosphate, preferably ammonium phosphate, using a volatile ester of phosphoric acid and ammonia (NH3).

[0027] German Patent No. 132126 describes the dehydration of 1,3-butanediol to 1,3-butadiene in a yield of about 90%, but the productivity is very low and the feed rate is low (0.0375 kg x h in Example 2). -1 ×l -1 (equivalent to).

[0028] Other methods have not yielded any better results. For example, a study on the reactivity of 2-buten-1-ol (crotyl alcohol) and 3-buten-2-ol (methyl vinyl carbinol) to produce 1,3-butadiene in an oxidizing environment using a bismuth molybdate type catalyst was reported by Adams CR, in “Exploratory catalytic oxidations with bismuth molybdate”, “Journal of catalysis” (1968), Vol. 10, pages 355-361). However, bismuth molybdate is reported to be a poor catalyst for the dehydration of 1,3-butanediol to 1,3-butadiene via 2-buten-1-ol (crotyl alcohol), as reported, for example, in Adams CR, in “Selectivity Effects in Some Catalytic Oxidation Processes”, “Industrial & Engineering Chemistry” (1969), Vol.61(6), pages 30-38 (DOI:10.1021 / ie50714a006).

[0029] Studies on the reactivity of alkenols with conjugated dienes other than 1,3-butadiene are also known.

[0030] For example, U.S. Patent Application No. 3,714,285 describes a process for preparing isoprene through the catalytic dehydration of 3-methyl-3-buten-1-ol (methylbutenol), which comprises contacting the 3-methyl-3-buten-1-ol (methylbutenol) with an acid catalyst, such as phosphoric acid supported on pumice, at elevated temperatures.

[0031] However, there are well-known drawbacks associated with the use of supported phosphoric acid-based catalysts, which require replacement of phosphoric acid lost during the reaction. These problems are also known in other contexts, such as, for example, the alkylation of aromatic compounds, as described in US Patent Application Publication No. 2005 / 075239, and highlight the fact that such catalysts pose environmental impacts and safety issues due to corrosion and disposal of spent catalysts.

[0032] The use of various dehydration catalysts is also known in the art.

[0033] For example, Weissermel K., Arpe HJ in “Industrial Organic Chemistry” (2008), 3rd Ed., John Wiley & Sons, page 117, reports the Snamprogetti process for producing isoprene from acetone-acetylene in the presence of alumina (Al2O3), which was used in Italy until the 1980s.

[0034] British Patent No. 935631 describes a method for producing a gas that is heated to 200m 2 A process for preparing isoprene is described by catalytic dehydration of 3-methyl-3-buten-1-ol (methylbutenol) using a catalyst consisting essentially of alumina (Al2O3) having a surface area greater than 100 nm / g at a temperature between 260°C and 270°C for a time between 1 second and 5 seconds.

[0035] It is also known to use silica-alumina (SiO2-Al2O3) as a catalyst in the production of 1,3-butadiene from alkenols, as described, for example, in Sato S. and others, in “Catalytic reaction of 1,3-butanediol over solid catalyst”, “Journal of Molecular Catalysis A: Chemical” (2006), Vol. 256, pages 106-112. In particular, Table 5 shows the conversion and selectivity values ​​to 1,3-butadiene obtained for 3-buten-1-ol, 2-buten-1-ol and 3-buten-2-ol, operating at 250° C., using silica-alumina (SiO2-Al2O3) as a catalyst. The values ​​obtained are as follows: 3-Buten-1-ol conversion=41.5%, selectivity to 1,3-butadiene=12.8%. 2-Buten-1-ol conversion=76.7%, selectivity to 1,3-butadiene=92.8%. 3-Buten-2-ol conversion=70.8%, selectivity to 1,3-butadiene=93.0%.

[0036] The silica-alumina (SiO2-Al2O3) used by Sato S. et al. is a product known under the trade name N631-L from Nikki Chemical Co., Ltd., and is 420 ml 2 / g and a Si / Al ratio of 5.4, corresponding to an alumina content (Al2O3) of about 13% (as reported in Example 1 of U.S. Pat. No. 3,689,477 and by Uemichi Y. and others, in “Chemical recycling of poly(ethylene) by catalytic degradation into aromatic hydrocarbons using H-Ga-silicate”, “Chemical communications” (1998), 1975-1976 DOI:10.1039 / A804927K).

[0037] However, the above documents merely report precise data, do not address the issue of catalyst decay, report low conversions (less than 80%), and use idealized feeds derived from the use of commercial and non-commercial alkenols derived from prior dehydration reactions (e.g., catalytic dehydration of diols to produce alkenols), thus failing to provide useful teachings targeted to industrial applications.

[0038] Similar conclusions can be drawn by consulting recent reviews, e.g., Makshina EV and others, “Review of old chemistry and new catalytic advances in the on-purpose synthesis of butadiene”, “Chemical Society Review” (2014), Vol. 43, pages 7917-7953 (DOI:10.1039 / C4CS00105B).

[0039] International patent application WO2013 / 130481 describes a process for preparing 1,3-butadiene by contacting 2-buten-1-ol (crotyl alcohol) produced by the recombinant host cells described therein with a solid acid catalyst, e.g. selected from silica-alumina (SiO2-Al2O3), under suitable operating conditions. However, even in this case there is no teaching regarding the specific catalyst and / or the specific method of using said catalyst.

[0040] Moreover, from the above, it is assumed that there is little information on the deactivation of acid catalysts in the dehydration of alkenols. In this regard, it is noted that it is known that dehydration of alcohols can occur via acid catalysis, the main products obtained being olefins with a carbon number corresponding to the starting alcohol or ethers of said alcohols, but that in addition to the main reaction, side reactions can also occur, such as, for example, dehydrogenation and / or oligomerization of olefins and / or cracking phenomena. These side reactions result in by-products that lead to the deactivation of the dehydration catalyst, as reported, for example, in Bartholomew CH, in “Mechanisms of catalyst deactivation” (2001), “Applied Catalysis A: General” Vol.212, p.17-60.

[0041] Optimization of catalyst systems and reaction conditions is a common approach to limit the processes that lead to catalyst deactivation, as described, for example, by Moulijn JA and others, in “Catalyst deactivation: is it predictable? What to do?”, “Applied Catalysis A: General” (2001), Vol. 212, pages 3-16.

[0042] WO 2016 / 135609 in the name of the applicant describes a process for producing dienes, preferably conjugated dienes, more preferably 1,3-butadiene, which comprises the dehydration of at least one alkenol in the presence of at least one catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3), preferably silica-alumina (SiO2-Al2O3), the alumina content of which is less than or equal to 12% by weight, preferably between 0.1% and 10% by weight, relative to the total weight of the catalyst. The use of said catalytic material is said to provide a number of advantages. For example, it is said that said catalytic material allows high conversion and selectivity values ​​to be obtained. Furthermore, said catalytic material is said to have a long life and to operate over a wide range of alkenol:diluent ratios. Moreover, the advantages are said to remain functional over a wide range of operating conditions, i.e., at different temperatures, different contact times (τ), allowing the use of different mixtures of alkenols, both mixtures of commercial alkenols and mixtures of alkenols derived from previous dehydration processes or direct biosynthesis processes. Moreover, the catalytic material, once regenerated, can be used again in the aforementioned processes for producing dienes, with allegedly excellent results.

[0043] The discovery of new processes for the dehydration of alkenols, more preferably butenols, even more preferably biobutenols derived from a biosynthetic process or from precursors obtained by a biosynthetic process, to 1,3-butadiene, in particular bio-1,3-butadiene, which can improve the aforementioned advantages, remains of great interest.

[0044] The Applicant therefore set himself the problem of finding a process for the production of dienes, in particular conjugated dienes, more particularly 1,3-butadiene and even more particularly bio-1,3-butadiene, which makes it possible to further improve the aforementioned advantages, in particular in terms of the producibility of dienes, in particular conjugated dienes, more particularly 1,3-butadiene and even more particularly bio-1,3-butadiene, by dehydration of at least one alkenol, in particular at least one alkenol originating from a biosynthetic process.

[0045] The Applicant has found that some of the catalytic materials described in the aforementioned WO 2016 / 135609, in particular catalytic materials comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3), in particular silica-alumina (SiO2-Al2O3), said catalyst having, in addition to the specific alumina content reported therein, specific pore characteristics, in particular specific pore mode diameters, can be advantageously used in the aforementioned process for producing dienes, in particular conjugated dienes, more particularly specific 1,3-butadienes, even more particularly bio-1,3-butadienes, and can further improve the aforementioned advantages.

[0046] In particular, the applicant has found that the use of said catalytic material allows for high performance in terms of duration and, consequently, productivity of each reaction cycle, reducing the need for regeneration between one cycle and another, which entails high costs and production losses. More specifically, the use of said catalytic material allows for a reduction in the amount of diene produced in grams per amount of catalytic material used in grams, i.e. (g ジエン / g 触媒 More specifically, as reported in the examples below, the use of the catalyst material can improve diene productivity, defined as the amount of 1,3-butadiene produced in grams per amount of catalyst material used in grams in a single cycle before the conversion falls below 80%, i.e., (g 1,3-BDE / g触媒 The productivity of 1,3-butadiene, defined as the product of the single cycle reaction, can be improved. Single cycle productivity is important because it minimizes catalyst regeneration, which is costly in terms of time and production loss. Furthermore, the catalytic material, once regenerated, can be used again in the aforementioned process for producing dienes with excellent results.

[0047] An object of the present invention is therefore a process for producing dienes, preferably conjugated dienes, more preferably 1,3-butadiene, comprising the dehydration of at least one alkenol in the presence of at least one catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3), preferably silica-alumina (SiO2-Al2O3), characterized in that the alumina content (Al2O3) is less than or equal to 12% by weight, preferably between 0.1% and 10% by weight relative to the total catalyst weight (the alumina content refers to the total catalyst weight without binder), and that the pore mode diameter is between 9 nm and 170 nm, preferably between 10 nm and 150 nm, even more preferably between 12 nm and 120 nm.

[0048] In this specification and the claims that follow, definitions of numerical intervals always include the end values, unless otherwise stated.

[0049] In this specification and the claims that follow, the term "comprising" also encompasses the terms "consisting essentially of" or "consisting of."

[0050] The pore mode diameter was determined according to the BJH method described in Barrett EP, Joyner LG and Haklenda PP et al., "Journal of the American Chemical Society" (1951), Vol. 73 (1), pp. 373-380 (1951) and the ASTM D4641-17 standard. In particular, the pore mode diameter was determined by plotting a pore size distribution curve calculated according to the BJH method from a desorption isotherm measured by nitrogen adsorption and desorption (BET method) at a temperature of liquid nitrogen equivalent to -196.15 ° C (77 K). The obtained experimental data was recorded using an ASAP2010 device from Micrometrics, and the calculations described in the aforementioned ASTM D4641-17 standard were automatically performed by the DataMaster software (trademark) (V4.03 March 2008) attached to the device, assuming the predetermined parameters described in the attached manual (page D-15).

[0051] According to a preferred embodiment of the present invention, the alkenol can be selected, for example, from 3-buten-2-ol (methylvinylcarbinol - CAS number 598-32-3), 3-buten-1-ol (allylcarbinol - CAS number 627-27-0), 2-buten-1-ol (crotyl alcohol) or mixtures thereof, preferably from 2-buten-1-ol (crotyl alcohol), 3-buten-2-ol (methylvinylcarbinol - CAS number 598-32-3) or mixtures thereof.

[0052] In this specification and the claims that follow, the term 2-buten-1-ol (crotyl alcohol) refers to both the mixture of cis and trans isomers and to the cis isomer itself (CAS No. 4088-60-2) and the trans isomer itself (CAS No. 504-61-0).

[0053] According to a preferred embodiment of the present invention, said alkenol can be obtained directly from a biosynthetic process or by a catalytic dehydration process of at least one diol, preferably butanediol, more preferably 1,3-butanediol, even more preferably bio-1,3-butanediol derived from a biosynthetic process.

[0054] Biosynthetic processes capable of directly producing alkenols are described, for example, in the above-reported WO 2013 / 130481 or in US Patent Application No. 2013 / 109064.

[0055] In the present invention, said alkenols can be obtained by catalytic dehydration of at least one diol, preferably at least one butanediol, more preferably 1,3-butanediol, even more preferably bio-1,3-butanediol derived from a biosynthetic process, in the presence of at least one catalyst based on cerium oxide, said catalyst based on cerium oxide being obtained by precipitation of at least one cerium-containing compound in the presence of at least one base. Further details regarding said process can be found in WO 2015 / 173780 in the name of the applicant, which is incorporated herein by reference.

[0056] According to a particularly preferred embodiment of the invention, said alkenol is derived from the catalytic dehydration of at least one diol, preferably butanediol, more preferably 1,3-butanediol, even more preferably bio-1,3-butanediol derived from sugar fermentation, preferably the fermentation of sugars derived from biomass.

[0057] In this specification and in the claims that follow, the term "biomass" refers to any organic material of plant origin, including: agricultural products, such as, for example, guayule, thistle, corn, soybean, cotton, flax, rapeseed, sugarcane, palm, including fragments, residues and waste from said products or from their processing; products from crops specifically grown for energy use, such as, for example, miscanthus, millet, reed, including fragments, residues and waste from said products or from their processing; products from afforestation or forestry, including fragments, residues and waste from said products or from their processing; fragments from agricultural products for human consumption or livestock production; residues from the paper industry; waste from the separate collection of urban solid waste, such as, for example, plant-based municipal waste, paper, etc.

[0058] Preferably, the diol is bio-1,3-butanediol derived from the fermentation of sugars derived from biomass (including fractions, residues or waste products derived from said biomass or fractions, residues or waste products derived from the processing thereof).

[0059] Even more preferably, the diol is bio-1,3-butanediol derived from the fermentation of sugars derived from guayule (including fractions, residues or waste products derived from said guayule or fractions, residues or waste products derived from the processing thereof).

[0060] When using lignocellulosic biomass from plants, in order to produce sugars, the biomass is subjected to physical treatments (e.g. extrusion, "steam explosion", etc.) and / or chemical and / or enzymatic hydrolysis, resulting in a mixture of carbohydrates, aromatic compounds and other products derived from the cellulose, hemicellulose and lignin present in the biomass. In particular, the carbohydrates obtained are a mixture of sugars with 5 and 6 carbon atoms, including, for example, sucrose, glucose, xylose, arabinose, galactose, mannose and fructose, which will be used for fermentation. Processes for the production of sugars from biomass are described in the art, for example in WO 2015 / 087254 in the name of the applicant. The fermentation is generally carried out by microorganisms, in particular genetically modified microorganisms, capable of producing the desired alcohol. Further details regarding processes for the synthesis of 1,3-butanediol, in particular bio-1,3-butanediol starting from renewable resources, can be found, for example, in US Patent Application No. 2010 / 330635, US Patent Application No. 2012 / 0329113 and US Patent Application No. 2013 / 0109064.

[0061] If the diol is derived from a biosynthetic process, e.g., from the fermentation of sugars, the resulting aqueous mixture of alkenols can be subjected to separation processes known in the art, such as, for example, total or partial distillation. Alternatively, the aqueous mixture of alkenols can be used as such, effectively using water as a diluent, without the need to subject the aqueous mixture to expensive water removal processes, or in any case limiting such removal.

[0062] When the alkenol is derived from the catalytic dehydration of at least one diol, the steps of dehydrating the at least one diol to obtain at least one alkenol and then dehydrating the at least one alkenol to obtain a diene can be In the same reactor or in different reactors, preferably in different reactors, Continuously or discontinuously, preferably discontinuously, Note that it may be possible to

[0063] In the present invention, said acid catalysts based on silica (SiO2) and alumina (Al2O3) can be obtained by processes known in the art and can be used in various forms, for example as described in WO 2016 / 135069, reported above in the name of the applicant and incorporated herein by reference. Further details regarding the process for preparing said catalysts can also be found in the examples below.

[0064] In the present invention, said acid catalysts based on silica (SiO2) and alumina (Al2O3) can be used as such or can be bound and / or formed by operating according to any process known in the art. Further details regarding the process can be found, for example, in U.S. Pat. No. 3,974,099, U.S. Pat. No. 4,226,743, U.S. Pat. No. 6,451,200, U.S. Pat. No. 4,499,197, U.S. Pat. No. 4,175,118, U.S. Pat. No. 5,045,519, U.S. Pat. No. 6,642,172 or Campanati M. et al., “Fundamentals in the preparation of heterogeneous catalysts”, “Catalysis Today” (2003), Vol. 77, pp. 299-314; Haber J. et al., “Manual of methods and procedures for catalyst characterization”, “Pure & Applied Chemistry” (1995), Vol. 67. No. 8-9, pp. 1257-1306.

[0065] According to a preferred embodiment of the present invention, said acid catalysts based on silica (SiO2) and alumina (Al2O3) are obtained by "incipient wetness impregnation", for example with a volume of a solution containing at least one alumina precursor, which may be chosen from aluminium alkoxides (e.g. tri-sec-aluminium butoxide), soluble aluminium salts (e.g. aluminium sulphate), aluminates (e.g. sodium aluminate), in a suitable concentration, equal to or slightly smaller than the pore volume of the solid support (e.g. silica).

[0066] According to a further preferred embodiment of the invention, said catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3) is obtainable by a process comprising: preparing an aqueous solution or suspension of alumina (Al2O3) or at least one precursor thereof, which may be selected from, for example, aluminum alkoxides (e.g., tri-sec-aluminum butoxide), soluble aluminum salts (e.g., aluminum sulfate), aluminates (e.g., sodium aluminate); adding to said aqueous solution or suspension of alumina (Al2O3) or at least one precursor thereof an aqueous solution or suspension of silica (SiO2) or at least one precursor thereof which may be selected from silicic acid (e.g. orthosilicic acid), alkali metal silicate (e.g. sodium silicate), The solid obtained by precipitation or gelation is collected and optionally subjected to subjecting the surface of the solid obtained to an ion exchange step with at least one compound capable of ion exchange, which may be selected, for example, from aqueous solutions of ammonium ion-containing salts (e.g., ammonium acetate, ammonium nitrate, ammonium sulfate); and / or subjecting it to a bonding step with at least one silica precursor (SiO), which may for example be chosen from colloidal silica (e.g. Ludox® TMA”) from Sigma-Aldrich, silica alkoxides (e.g. tetraethyl orthosilicate), or at least one alumina precursor (AlO), which may for example be chosen from boehmite or pseudoboehmite (such as Versal® V-250 from UOP); and / or For example, subjecting the mixture to a molding process such as extrusion, spheronization, tableting, or granulation; subjecting it to an optional heat treatment and / or optional calcination, which may be carried out before or after any of the aforementioned steps, i.e. ion-exchange and / or bonding and / or shaping.

[0067] It is noted that in the present invention, said aqueous solution or suspension of alumina (Al2O3) or said aqueous solution or suspension of at least one of its precursors can be added in one or more steps to said aqueous solution or suspension of silica (SiO2) or said aqueous solution or suspension of at least one of its precursors.

[0068] It is noted that in the present invention, said aqueous solution or suspension of alumina (SiO2) or of at least one of its precursors can be added in one or more steps to said aqueous solution or suspension of silica (Al2O3) or of at least one of its precursors.

[0069] The above-mentioned addition can be carried out using methods known in the art and can also refer to conventional test protocols (for example, by weighing, by volumetric administration, etc., without limiting the scope of the present invention). However, the addition steps can be more than two without constituting a criticality and thus a limitation of the present invention.

[0070] In the present invention, said aqueous solution or suspension of alumina (Al2O3) or said aqueous solution or suspension of at least one precursor thereof may constitute 0.1% by weight to 70% by weight, preferably 0.3% by weight to 60% by weight, even more preferably 0.5% by weight to 50% by weight, based on the total weight of said aqueous solution or suspension of alumina (Al2O3) or said aqueous solution or suspension of at least one precursor thereof.

[0071] Alternatively, instead of said aqueous solution or suspension of alumina (Al2O3) or of at least one precursor thereof, an aqueous alcoholic solution (containing 0.1 wt. % to 95 wt. %, preferably 0.3 wt. % to 60 wt. %, even more preferably 0.5 wt. % to 30 wt. % of at least one alcohol (e.g. selected from ethanol, 2-methoxyethanol, n-propanol, iso-propanol, n-butanol, iso-butanol, tert-butanol or mixtures thereof) relative to the total weight of said aqueous alcoholic solution) can be used.

[0072] In the present invention, said aqueous solution or suspension of silica (SiO2) or of at least one precursor thereof may contain 5 wt. % to 70 wt. %, preferably 10 wt. % to 60 wt. %, even more preferably 15 wt. % to 50 wt. % of silica (SiO2) or of at least one precursor thereof, based on the total weight of said aqueous solution or suspension of silica (SiO2) or of at least one precursor thereof.

[0073] Alternatively, instead of said aqueous solution or suspension of silica (SiO2) or of at least one precursor thereof, an aqueous alcoholic solution can be used, which comprises 5% to 95% by weight, preferably 15% to 60% by weight, even more preferably 20% to 30% by weight of at least one alcohol (e.g. selected from ethanol, 2-methoxyethanol, n-propanol, iso-propanol, n-butanol, iso-butanol, tert-butanol or mixtures thereof) relative to the total weight of said aqueous alcoholic solution.

[0074] The solids obtained from the above process may be recovered via processes known in the art, such as, for example, filtration, decantation, and the like.

[0075] The above-mentioned possible heat treatment may be carried out at a temperature of 100° C. to 200° C., preferably 105° C. to 150° C., for a period of 2 hours to 72 hours, preferably 3 hours to 18 hours.

[0076] The optional calcination may be carried out at a temperature of 150° C. to 1500° C., preferably 200° C. to 1400° C., and even more preferably 300° C. to 1200° C., for a period of 1 hour to 24 hours, preferably 2 hours to 10 hours, and even more preferably 4 hours to 8 hours. In general, the calcination may be carried out in air or in an inert gas [such as nitrogen (N2)] or in a controlled atmosphere (oxidizing or reducing), preferably in air.

[0077] As mentioned above, the acid catalysts based on silica (SiO2) and alumina (Al2O3), if not obtained by incipient wetness impregnation, can be used in various forms. For example, the catalysts can be used as such or can be shaped by operating according to any shaping process known in the art, such as extrusion, spheronization, tableting, granulation, etc. Any heat treatment and any calcination reported above can be carried out before or after any of the shaping processes.

[0078] Preferably, said acid catalysts based on silica (SiO2) and alumina (Al2O3), if not obtained by incipient wetness impregnation, may be used in extruded form, optionally comprising conventional binders such as alumina (Al2O3), silica (SiO2), zirconium oxide, titanium oxide, preferably silica (SiO2) or alumina (Al2O3), even more preferably alumina (Al2O3).

[0079] When said conventional binders are present, extrusion also provides for the use of a deflocculating agent, such as, for example, an aqueous solution of acetic acid, nitric acid or ammonium hydroxide, which may be mixed with the catalyst and binder before extrusion until a homogeneous mixture is obtained. At the end of said extrusion, the pellets obtained are usually subjected to calcination by the operations described above.

[0080] The solid obtained after binding and / or shaping may contain 5% to 90% by weight, preferably 10% to 75% by weight, more preferably 20% to 55% by weight of binder relative to the total weight of said acid catalyst based on silica (SiO2) and alumina (Al2O3).

[0081] It is noted that after bonding and / or shaping, the pore mode diameter of said catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3) is in the range reported above, i.e. 9 nm - 170 nm, preferably 10 nm - 150 nm, even more preferably 12 nm - 120 nm.

[0082] According to a preferred embodiment of the present invention, the pore mode diameter of said catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3) obtained after bonding and / or shaping is between 9 nm and 170 nm, preferably between 10 nm and 150 nm, even more preferably between 12 nm and 120 nm.

[0083] According to a preferred embodiment of the present invention, the acid catalyst based on silica (SiO2) and alumina (Al2O3) has a specific surface area of ​​40 m 2 / g~800m2 / g, preferably 45m 2 / g~700m 2 / g, and even more preferably 50m 2 / g~600m 2 / g.

[0084] According to a preferred embodiment of the present invention, the catalytic material comprises at least one acid catalyst based on silica (SiO2) and alumina (Al2O3) and at least one binder which may for example be selected from alumina (Al2O3), silica (SiO2), zirconium oxide, titanium oxide, preferably silica (SiO2) or alumina (Al2O3), even more preferably alumina (Al2O3).

[0085] According to a further preferred embodiment of the present invention, the catalytic material, which comprises at least one acid catalyst based on silica (SiO2) and alumina (Al2O3) and at least one binder selected from alumina (Al2O3) or silica (SiO2), and / or which has been subjected to shaping, has a specific surface area of ​​25 m 2 / g~700m 2 / g, preferably 100m 2 / g~600m 2 / g, and even more preferably 110m 2 / g~500m 2 / g.

[0086] In this specification and in the following claims, the term "specific surface area" refers to the BET specific surface area determined by static adsorption of nitrogen (N2) at the temperature of liquid nitrogen equivalent to -196.15°C (77K) using an ASAP 2010 instrument from Micromeritics according to the ASTM D3663-03 (2008) standard.

[0087] Elemental analysis of the silica (SiO2) and alumina (Al2O3) based acid catalysts was performed by WD-XRF ("wavelength dispersive X-ray fluorescence") using a PANalytical Axios Advanced spectrometer equipped with a 4KW X-ray tube with a rhodium (Rh) anode.

[0088] According to a preferred embodiment of the present invention, the implementation of said process for producing dienes may be carried out using a diluent, which may be selected from, for example, an inert gas such as nitrogen (N2), argon (Ar), preferably nitrogen (N2); or a compound having a boiling point of 50° C. or more and a melting point of 40° C. or less, preferably a compound in the liquid state at ambient temperature (25° C.) and ambient pressure (1 atm), for example water, tetrahydrofuran, cyclohexane, benzene, etc. Nitrogen (N2), water are preferred, water being particularly preferred.

[0089] According to a preferred embodiment of the present invention, the implementation of said process for producing dienes may be carried out at a molar ratio of diluent to alkenol of greater than 0.3, preferably between 0.5 and 2, when the diluent is selected from inert gases.

[0090] According to a preferred embodiment of the present invention, the implementation of said process for producing dienes may be carried out at a molar ratio of diluent to alkenol of 0.01 to 100, preferably 0.1 to 50, more preferably 1 to 10, when the diluent is selected from compounds having a boiling point equal to or higher than 50° C. and a melting point equal to or lower than 40° C., preferably compounds that are in the liquid state at ambient temperature (25° C.) and ambient pressure (1 atm).

[0091] According to a preferred embodiment of the present invention, the process for producing dienes may be carried out at a temperature of 150°C to 500°C, preferably 200°C to 450°C, more preferably 250°C to 400°C.

[0092] According to a preferred embodiment of the invention, the implementation of said process for producing dienes may be carried out at a pressure between 0.05 bara and 50 bara, preferably between 0.3 bara and 3.5 bara, more preferably between 0.8 bara and 2.5 bara (bara = absolute bar).

[0093] According to a preferred embodiment of the present invention, the implementation of the process for producing dienes can be performed with a contact time (τ), calculated as the ratio of the loading amount of catalyst material to the feed volume, of 0.01 seconds to 10 seconds, preferably 0.05 seconds to 8 seconds, more preferably 0.1 seconds to 4 seconds.

[0094] According to a preferred embodiment of the present invention, the pretreatment of said catalytic material comprising at least one acid catalyst based on silica (SiO2) and alumina (Al2O3), preferably silica-alumina (SiO2-Al2O3), may be carried out at the operating temperature of said process for producing dienes, i.e. between 150°C and 500°C, preferably between 200°C and 450°C, more preferably between 250°C and 400°C, preferably in the presence of at least one diluent selected from those reported above, more preferably in the presence of water.

[0095] In the present invention, the process for producing dienes can be carried out in gas phase or in a mixed liquid / gas phase, preferably in gas phase, discontinuously (for example in a stirred and heated autoclave) or continuously (for example in one or more catalytic reactors in series), preferably continuously. The reactors can be fixed bed or fluidized bed, but preferably fixed bed. If they are fixed bed, the catalytic material can be distributed in several beds. The reactors can be expected to recycle part of the reaction effluent or catalytic material by constituting a recycle reactor. If a liquid phase is present, the process for producing dienes can be carried out in a continuous stirred reactor with dispersed catalytic material.

[0096] In order to better understand and to put the present invention into practice, some illustrative, non-limiting examples thereof are reported below.

[0097] (Example 1 (Comparative Example)) (Preparation of silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) of 1.8% and a pore mode diameter of 7 nm) 3360.3 g of an aqueous solution of sodium silicate (Aldrich) as silica precursor (SiO2) corresponding to a silica content (SiO2) of 26.5% were introduced into a first 5 L flask. 26.6 g of sodium aluminate (Al2O3) as alumina precursor (Al2O3) (Aldrich) and 650.9 g of demineralized water were introduced into a second 2 L flask to obtain a second aqueous solution. The second aqueous solution was poured into the 5 L flask and the solution obtained was kept at ambient temperature (25°C) for 1 hour with vigorous stirring (500 rpm) to obtain a suspension which was then heated to 80°C and kept at said temperature for 1 hour with vigorous stirring (500 rpm). After cooling to ambient temperature (25°C), the pH of the suspension obtained was brought from pH 13 to pH 12 by adding a 96% sulfuric acid solution (Aldrich) to obtain a colorless gel. The gel obtained was granulated, transferred to a 12 L plastic container and treated four times with 500 mL of 10% aqueous ammonium sulfate (Aldrich). The material was filtered, washed with 10 L of demineralized water, dried overnight at 120 °C and then calcined at 500 °C for 5 h to obtain silica-alumina (SiO2-Al2O3) (936 g) in the form of a colorless powder, the elemental analysis of which, as described above, showed an alumina content (Al2O3) equivalent to 1.8%. The silica-alumina (SiO2-Al2O3) had a BET specific surface area of ​​259 m, determined as reported above. 2 / g, corresponding to a pore mode diameter of 7 nm, determined as reported above.

[0098] (Example 2 (Comparative Example)) (Preparation of a catalyst based on silica-alumina (SiO2-Al2O3) containing an alumina binder (Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 3 nm) A 63.8 g portion of the silica-alumina (SiO2-Al2O3) obtained in Example 1 was mixed with 30.8 g of pseudoboehmite Versal™ V-250 (UOP) as the alumina precursor of the binder (Al2O3) and 300 mL of a 4% solution of acetic acid (Aldrich) in a 500 mL beaker. The mixture obtained was kept at 60° C. for about 2 hours with vigorous stirring (500 rpm). The beaker was then transferred onto a heating plate and the mixture was kept at 150° C. overnight with vigorous stirring (500 rpm) until it was dry. The solid obtained was calcined at 550° C. for 5 hours to obtain 84 g of silica-alumina (SiO2-Al2O3) in the form of a colorless solid containing the alumina binder (Al2O3), which was then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as the catalyst material. The silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) has a BET specific surface area of ​​254 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 3 nm, determined as reported above.

[0099] (Example 3 (invention example)) (Preparation of silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equivalent to 1.8% and a pore mode diameter equivalent to 14 nm) In a first 5 L flask, 1056.8 g of an aqueous solution of sodium silicate (Aldrich) with a silica content of 26.5% as silica precursor (SiO2) and 786.6 g of demineralized water were introduced. In a second 2 L flask, 8.5 g of sodium aluminate (Al2O3) as alumina precursor (Al2O3) and 1199.1 g of demineralized water were introduced to obtain a second aqueous solution. The second aqueous solution was poured into the 5 L flask and the solution obtained was kept at ambient temperature (25°C) for 1 hour with vigorous stirring (500 rpm) to obtain a suspension which was then heated to 80°C and kept at said temperature for 1 hour with vigorous stirring (500 rpm). After cooling to ambient temperature (25°C), the pH of the suspension obtained was brought from pH 13 to pH 8.5 by adding a 96% sulfuric acid solution (Aldrich) to obtain a colorless gel. The gel obtained was transferred to a 12 L plastic container and treated four times with 5 kg of 10% aqueous ammonium sulfate (Aldrich) solution to obtain a solid which was filtered, washed with 10 kg of demineralized water, dried overnight at 120 °C and then calcined at 500 °C for 5 h to obtain silica-alumina (SiO2-Al2O3) (236 g) in the form of a colorless powder, the elemental analysis of which was carried out as described above and corresponds to an alumina content (Al2O3) of 1.8%. The silica-alumina (SiO2-Al2O3) has a BET specific surface area of ​​262 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 14 nm, determined as reported above.

[0100] (Example 4 (invention example)) (Preparation of a catalyst based on silica-alumina (SiO2-Al2O3) containing an alumina binder (Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 14 nm) A 26.6 g portion of the silica-alumina (SiO2-Al2O3) obtained in Example 3 was mixed with 14.7 g of pseudoboehmite Versal™ V-250 (UOP) as the alumina precursor (Al2O3) of the binder and 300 mL of a 4% solution of acetic acid (Aldrich) in a 500 mL beaker. The mixture obtained was kept at 60° C. for about 2 hours with vigorous stirring (500 rpm). The beaker was then transferred onto a heating plate and the mixture was kept at 150° C. overnight with vigorous stirring (500 rpm) until it was dry. The solid obtained was calcined at 550° C. for 5 hours to obtain silica-alumina (SiO2-Al2O3) (34 g) in the form of a colorless solid containing the alumina binder (Al2O3), which was then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as the catalyst material. The silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) had a BET specific surface area of ​​255 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 14 nm, determined as reported above.

[0101] (Example 5 (invention example)) (Preparation of silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) of 1.8% and a pore mode diameter of 40 nm) In a first 5 L flask, 1057.3 g of an aqueous solution of sodium silicate (Aldrich) with a silica content (SiO2) of 26.5% was introduced as silica precursor (SiO2) and 787.0 g of demineralized water. In a second 2 L flask, 9.0 g of sodium aluminate (Aldrich) as alumina precursor (Al2O3) and 1219.8 g of demineralized water were introduced to obtain a second aqueous solution. The second aqueous solution was poured into the 5 L flask and the solution obtained was kept at ambient temperature (25°C) for 1 hour with vigorous stirring (500 rpm) to obtain a suspension which was then heated to 80°C and kept at that temperature for 1 hour with vigorous stirring (500 rpm). After cooling to ambient temperature (25° C.), the pH of the suspension obtained was brought from pH 13 to pH 8.5 by adding a 96% sulfuric acid solution (Aldrich) and the whole was kept under stirring at ambient temperature (25° C.) for 72 hours, obtaining a colorless gel. The colorless gel obtained was transferred to a 12 L plastic container and treated four times with 5 kg of a 10% aqueous solution of ammonium sulfate (Aldrich), obtaining a solid. The solid was filtered, washed with 10 kg of demineralized water, dried overnight at 120° C. and then calcined at 500° C. for 5 hours, obtaining silica-alumina (SiO2-Al2O3) (252.8 g) in the form of a colorless powder, the elemental analysis of which was carried out as described above, and the alumina content (Al2O3) was equal to 1.8%. The silica-alumina (SiO2-Al2O3) had a BET specific surface area of ​​221 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 40 nm, determined as reported above.

[0102] (Example 6 (invention example)) Preparation of a catalyst based on silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 37 nm, containing an alumina binder (Al2O3) A 100.1 g portion of the silica-alumina (SiO2-Al2O3) obtained in Example 5 was mixed with 55.2 g of pseudoboehmite Versal™ V-250 (UOP) as the alumina precursor (Al2O3) of the binder and 300 mL of a 4% solution of acetic acid (Aldrich) in a 500 mL beaker. The mixture obtained was kept at 60° C. for about 2 hours with vigorous stirring (500 rpm). The beaker was then transferred onto a heating plate and the mixture was kept at 150° C. overnight with vigorous stirring (500 rpm) until it was dry. The solid obtained was calcined at 550° C. for 5 hours to obtain silica-alumina (SiO2-Al2O3) (138 g) in the form of a colorless solid containing the alumina binder (Al2O3), which was then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as the catalyst material. The silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) has a BET specific surface area of ​​212 m2 determined as reported above. 2 / g, corresponding to a pore mode diameter of 37 nm, determined as reported above.

[0103] (Example 7 (invention example)) (Preparation of silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equivalent to 1.8% and a pore mode diameter equivalent to 37 nm) In a first 5 L flask, 1056.9 g of an aqueous solution of sodium silicate (Aldrich) with a silica content (SiO2) of 26.5% was introduced as silica precursor (SiO2) and 787.9 g of demineralized water. In a second 2 L flask, 9.0 g of sodium aluminate (Aldrich) as alumina precursor (Al2O3) and 1219.2 g of demineralized water were introduced to obtain a second aqueous solution. The second aqueous solution was poured into the 5 L flask and the solution obtained was kept at ambient temperature (25°C) for 1 hour with vigorous stirring (500 rpm) to obtain a suspension which was then heated to 80°C and kept at that temperature for 1 hour with vigorous stirring (500 rpm). After cooling to ambient temperature (25° C.), the pH of the suspension obtained was brought from pH 13 to pH 8.5 by adding a 70% nitric acid solution (Aldrich) and the whole was kept under stirring at ambient temperature (25° C.) for 72 hours, obtaining a colourless gel. The colourless gel obtained was transferred to a 12 L plastic container and treated four times with 5 kg of a 10% aqueous solution of ammonium sulphate (Aldrich) to obtain a solid. The solid was filtered, washed with 10 kg of demineralised water, dried overnight at 120° C. and then calcined at 500° C. for 5 hours, obtaining silica-alumina (SiO2-Al2O3) (254.5 g) in the form of a colourless powder, the elemental analysis of which was carried out as described above, giving an alumina content (Al2O3) equal to 1.8%. The silica-alumina (SiO2-Al2O3) had a BET specific surface area of ​​252 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 37 nm, determined as reported above.

[0104] (Example 8 (invention example)) Preparation of a (extruded) catalyst based on silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 36 nm, containing an alumina binder (Al2O3) A portion of the silica-alumina (SiO2-Al2O3) obtained in Example 7 was subjected to extrusion processing. For this purpose, 100.1 g of said silica-alumina (SiO2-Al2O3) and 86.6 g of pseudoboehmite Versal™ V-250 (UOP) as alumina precursor (Al2O3) of the binder were introduced into an Erweka AR 402 mixer and the powder was mixed for 2 hours at a rotation speed of 80 rpm. Then, 253.0 g of a 5% solution of acetic acid was added and the mixture was mixed for another 2 hours at a rotation speed of 80 rpm. The mixture was then transferred to a Hosokawa-Bepex Pharmapaktor L 200 / 50G laboratory extruder, operated under the following conditions: Temperature: 25℃ Screw rotation speed: 15 rpm Pressure: 150kN

[0105] Pellets were obtained at the extruder outlet, which were dried in air and then calcined at 550 °C for 5 h. 133.7 g of silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) was obtained in the form of a colourless solid, which was then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as catalyst material. The silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) had a BET specific surface area of ​​260 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 36 nm, determined as reported above.

[0106] (Example 9 (invention example)) (Preparation of silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equivalent to 1.8% and a pore mode diameter equivalent to 100 nm) 251.4 g of an aqueous solution of sodium silicate (Aldrich) with a silica content of 26.5% as silica precursor (SiO2) and 105.0 g of demineralized water were introduced into a first 1 L flask. 1.8 g of sodium aluminate (Aldrich) as alumina precursor (Al2O3), 11.1 g of sodium dihydrogen phosphate (NaH2PO4·H2O) (Aldrich) and 255.0 g of demineralized water were introduced into a second 1 L flask to obtain a second aqueous solution. The second aqueous solution was poured into a 1 L flask and the solution obtained was kept at ambient temperature (25 °C) for 1 hour with vigorous stirring (500 rpm) to obtain a suspension which was then heated to 80 °C and kept at said temperature for 1 hour with vigorous stirring (500 rpm). After cooling to ambient temperature (25°C), the pH of the suspension obtained was brought from pH 13 to pH 8.5 by adding a 96% sulfuric acid solution (Aldrich), obtaining a colourless gel. The gel obtained was transferred to a 5 L plastic container and treated four times with 2 kg of a 10% aqueous solution of ammonium acetate (Aldrich), obtaining a solid. The solid was filtered, washed with 500 g of demineralised water, dried overnight at 120°C and then calcined at 500°C for 5 hours, obtaining silica-alumina (SiO2-Al2O3) (54 g) in the form of a colourless powder, the elemental analysis of which was carried out as described above, giving an alumina content (Al2O3) equal to 1.8%. The silica-alumina (SiO2-Al2O3) had a BET specific surface area, determined as reported above, of 57 m 2 / g, and the pore mode diameter, determined as reported above, corresponds to 100 nm.

[0107] (Example 10 (invention example)) Preparation of a catalyst based on silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 100 nm, containing an alumina binder (Al2O3) A 20.0 g portion of the silica-alumina (SiO2-Al2O3) obtained in Example 9 was mixed with 12.0 g of pseudoboehmite Versal™ V-250 (UOP) as the alumina precursor (Al2O3) of the binder and 300 mL of a 4% solution of acetic acid (Aldrich) in a 500 mL beaker. The mixture obtained was kept at 60° C. for about 2 hours with vigorous stirring (500 rpm). The beaker was then transferred onto a heating plate and the mixture was kept at 150° C. overnight with vigorous stirring (500 rpm) until it was dry. The solid obtained was calcined at 550° C. for 5 hours to obtain silica-alumina (SiO2-Al2O3) (28 g) in the form of a colorless solid containing the alumina binder (Al2O3), which was then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as the catalyst material. The silica-alumina (SiO2-Al2O3) with alumina binder (Al2O3) has a BET specific surface area of ​​118 m2, determined as reported above. 2 / g, and the pore mode diameter, determined as reported above, corresponds to 100 nm.

[0108] (Example 11 (Comparative Example)) Preparation of a (extruded) catalyst based on silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 3 nm A portion of the silica-alumina (SiO2-Al2O3) prepared in Example 1 was subjected to extrusion processing. For this purpose, 450.1 g of said silica-alumina (SiO2-Al2O3) and 217.0 g of pseudoboehmite Versal™ V-250 (UOP) as alumina precursor (Al2O3) of the binder were introduced into an Erweka AR 402 planetary mixer. The powders were mixed for 2 hours at a rotation speed equivalent to 80 rpm. Then, 766.1 g of a 4% solution of acetic acid (Aldrich) were fed, while maintaining the rotation speed of the mixer equivalent to 80 rpm. The mixture was then transferred to a Hosokawa-Bepex Pharmapaktor L 200 / 50G laboratory extruder, operated under the following conditions: Temperature: 25℃ Screw rotation speed: 15 rpm Pressure: 150kN

[0109] At the exit of the extruder, pellets were obtained, which were dried in air and then calcined at 550 °C for 5 h. 300.6 g of silica-alumina (SiO2-Al2O3) in the form of a colourless solid containing an alumina binder (Al2O3) were obtained, which were then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as catalyst material. The silica-alumina (SiO2-Al2O3) containing an alumina binder (Al2O3) had a BET specific surface area of ​​252 m2, determined as reported above. 2 / g, corresponding to a pore mode diameter of 3 nm, determined as reported above.

[0110] (Example 12 (invention example)) Preparation of a (extruded) catalyst based on silica-alumina (SiO2-Al2O3) with an alumina content (Al2O3) equal to 1.8% and a pore mode diameter equal to 36 nm, containing an alumina binder (Al2O3) A portion of the silica-alumina (SiO2-Al2O3) prepared in Example 5 was subjected to extrusion processing. For this purpose, 103.0 g of said silica-alumina (SiO2-Al2O3) and 57.0 g of pseudoboehmite Versal™ V-250 (UOP) as alumina precursor (Al2O3) of the binder were introduced into an Erweka AR 402 planetary mixer. The powders were mixed for 2 hours at a rotation speed equivalent to 80 rpm. Then, 450.0 g of a 4% solution of acetic acid (Aldrich) were fed, while maintaining the rotation speed of the mixer equivalent to 80 rpm. The mixture was then transferred to a Hosokawa-Bepex Pharmapaktor L 200 / 50G laboratory extruder, operated under the following conditions: Temperature: 25℃ Screw rotation speed: 15 rpm Pressure: 150kN

[0111] At the extruder outlet, pellets were obtained, which were dried in air and then calcined at 550 °C for 5 h. 98.6 g (138 g) of silica-alumina (SiO2-Al2O3) in the form of a colourless solid containing an alumina binder (Al2O3) were obtained, which were then mechanically granulated and the fraction of granules with dimensions between 0.5 mm and 1.0 mm was used as catalyst material. The silica-alumina (SiO2-Al2O3) containing an alumina binder (Al2O3) had a BET specific surface area of ​​226 m, determined as reported above. 2 / g, corresponding to a pore mode diameter of 36 nm, determined as reported above.

[0112] Table 1 shows the various types of catalysts obtained in Examples 1-12. [Table 1]

[0113] From the comparison of Example 1 (Comparative Example), Example 3 (Inventive Example), Example 5 (Inventive Example), Example 7 (Inventive Example) and Example 9 (Inventive Example), it can be seen that it is possible to obtain a catalyst having a pore mode diameter according to the present invention by suitable means, such as pH variation at one stage of the silica-alumina synthesis (SiO2-Al2O3), increasing aging at another stage of the synthesis, or finally using a compound with pore-forming or template function, such as a compound containing a heteroatom such as phosphorus (P) (for example, as reported in Wen Wen et al., "Effect of sol ageing time on the anti-reflective properties of silica coatings templated with phosphoric acid", "Results in Physics" (2016), pages 1012-1014, https: / / doi.org / 10.1016 / j.rinp2016.11.028). It should be noted that in the present invention, the means are intended as examples and are not limiting. The pore mode diameter according to the present invention can also be obtained by other methods.

[0114] A comparison of Example 3 (inventive example) and Example 4 (inventive example) shows that the pore mode diameter after bonding is in accordance with the present invention.

[0115] Comparison of Example 7 (inventive example) with Example 8 (inventive example) shows that the pore mode diameter after bonding and extrusion is in accordance with the present invention.

[0116] A comparison of Examples 5 (inventive), 6 (inventive) and 12 (inventive) shows that the pore mode diameters after bonding (Example 6) and after extrusion (Example 12) are in accordance with the present invention.

[0117] Finally, a comparison of Examples 1 (Comparative), 2 (Comparative) and 11 (Comparative), which started with catalysts having pore mode diameters outside the scope of the invention, shows that the pore mode diameters after bonding (Example 2) and extrusion (Example 11) are not in accordance with the invention.

[0118] (Examples 13-18) (Catalyst Testing) The catalytic materials obtained in Examples 1 to 12 were used in tests for the catalytic dehydration of a mixture of butenols obtained by catalytic dehydration of 1,3-butanediol, operating as described in Examples 8 to 15 of WO 2016 / 135609 reported above.

[0119] The mixture of butenols obtained at the outlet of the reactor was distilled to obtain an aqueous solution of isomeric butenols having the compositions reported in Table 2. [Table 2]

[0120] Aqueous solutions of butenol reported in Table 2 were diluted with water as reported in Table 3 and subjected to catalytic dehydration operated as follows.

[0121] The reactor in which the catalytic dehydration reaction was carried out was a tubular reactor with a length of 350 mm and an internal diameter of 9.65 mm, equipped with a fixed bed made of AISI 316L steel. Inside the reactor, along its axis, there was a well corresponding to an external diameter of 3 mm, which housed a thermocouple for temperature regulation. The reactor was placed in an electrically heated oven, which made it possible to reach the temperature selected for the reaction.

[0122] The catalyst equivalent to 3 g was inserted between two layers of inert material (corundum) and the catalyst bed was held in place by a sintered steel septum placed at the bottom of the downflow reactor.

[0123] The feed was made from the top of the reactor, above an area filled with inert material, which acted as an evaporator and allowed the reactants to reach reaction temperature before contacting the catalyst.

[0124] Liquid reagents were fed by metering pumps of the type used in "High Performance Liquid Chromatography" (HPLC). Gases were fed through "thermal mass flow meters" (TMF). Downstream of the reactor, the resulting product was cooled in a heat exchanger and the condensate was collected in glass bottles by a series of timed valves. The non-condensed gas was instead sent to a volumetric wet gas meter to measure the volume of gas produced. A portion of the gas was sampled for analysis by an on-line gas chromatograph (GC). On-line gas analysis was performed with an Agilent HP7890 gas chromatograph (GC) on a 50 m long HP-Al / S column (diameter 0.53 mm, film thickness 15 microns), the carrier used was helium with a flow rate of 30 cm / s, and the detector was a flame detector. Gas analysis was performed by a calibration method of single known components using external standards.

[0125] The collected liquid was characterized by gas chromatographic analysis using an Agilent HP6890 gas chromatograph (GC) equipped with a "Split / Splitless" injector on a 25 m high Quadrex 007 FFAP column (0.32 mm diameter, 1 micron film thickness), the carrier used was helium with a velocity equivalent to 50 cm / sec, and the detector was a flame detector. Measurements were performed by calibration of single known components using internal standards.

[0126] The catalytic material in the form of granules with dimensions between 0.5 mm and 1 mm, used in an amount equivalent to 3 g, was prepared as described above in Examples 2 (Comparative), 4 (Inventive), 6 (Inventive), 8 (Inventive), 10 (Inventive), 11 (Comparative) and 12 (Inventive).

[0127] Table 3 shows the catalyst used (catalyst), the temperature at which the catalytic dehydration is carried out [T (°C)], the contact time [τ (sec)] calculated as the ratio of the volume of the loaded catalyst material to the feed volume, the dilution carried out, i.e. the molar ratio of water to butenol fed [dilution (mol / mol)] obtained by adding an appropriate amount of water to the butenol mixture, and the productivity of 1,3-butadiene, defined as the amount of 1,3-butadiene produced in grams relative to the amount of catalyst material used in grams, in a single cycle reached before the conversion falls below 80% (g 1,3-BDE / g 触媒 ) [Table 3]

[0128] From the data reported in Table 3, it can be seen that: From a comparison between Example 13 (Comparative Example) and Example 14 (Inventive Example), it can be seen that the silica-alumina (SiO2-Al2O3) having a pore mode diameter of more than 10 nm according to the present invention has higher manufacturability (g 1,3-BDE / g 触媒 ) can be obtained. From the comparison of Example 13 (Comparative Example), Example 14 (Inventive Example) and Example 15 (Inventive Example), it can be seen that the silica-alumina (SiO2-Al2O3) having the pore mode diameter according to the present invention, which is obtained thanks to the increase in gel aging during the synthesis stage, has high manufacturability (g 1,3-BDE / g 触媒 ) can be obtained. Comparison of Example 13 (comparative example) and Example 16 (inventive example) shows that the silica-alumina (SiO2-Al2O3) with the pore mode diameter according to the present invention obtained thanks to the use of NaH2PO4·H2O in the synthesis step has high manufacturability (g 1,3-BDE / g 触媒 ) can be obtained. From the comparison of Example 17 (Comparative Example), Example 18 (Inventive Example) and Example 19 (Inventive Example), it can be seen that the silica-alumina (SiO2-Al2O3) having the pore mode diameter according to the present invention obtained by extrusion has high manufacturability (g 1,3-BDE / g 触媒 ) can be obtained.

[0129] (Example 19) (Catalyst Life Test of Example 8) The catalyst obtained as described in Example 8 was subjected to a life test consisting of a series of reaction cycles followed by regeneration when the reactant conversion fell below 80%.

[0130] The regeneration was carried out in the following manner: the catalyst was packed into a tubular reactor, 350 mm long and 9.65 mm in internal diameter, equipped with a fixed bed made of AISI 316L, and was subjected to a nitrogen flow (GHSV=1500 h 2 O) in order to remove therefrom any volatile organic compounds present. -1 The temperature was maintained at 450°C in nitrogen (N2) for 1 hour. Air was then gradually introduced into the reactor, its concentration gradually increasing until the air supply was completed within a 4 hour period. Regeneration continued for another 24 hours, at the end of which the catalyst was cooled to its reaction temperature in nitrogen (N2) and used in the next reaction cycle.

[0131] Table 4 shows, for some reaction cycles carried out, the following parameters: [number of cycles (reaction / regeneration)]; reaction time ("Time on Stream" - ToS) (hours), i.e., the time the catalyst was in contact with the feed stream under process conditions before the conversion fell below 80%; contact time [τ (seconds)], calculated as the ratio of the loaded catalyst material to the feed volume; dilution used, i.e., the molar ratio of water to butenol fed, obtained by adding an appropriate amount of water to the butenol mixture [dilution (mol / mol)]; and the producibility of 1,3-butadiene, defined as the amount of 1,3-butadiene produced in grams per amount of catalyst material used in grams in a single cycle reached before the conversion fell below 80% (g 1,3-BDE / g 触媒 ) [Table 4]

[0132] From the data reported in Table 4, it can be seen that the silica-alumina (SiO2-Al2O3) of Example 8 having the pore mode diameter according to the present invention has good manufacturability (g) even after several reaction / regeneration cycles. 1,3-BDE / g 触媒 Moreover, the catalyst has been regenerated for a total duration of more than 4000 hours and has undergone 38 regenerations to reach 39 reaction cycles without ever showing signs of decay, with an average productivity of 140 grams (g 1,3-BDE / g 触媒 ) is maintained.

Claims

1. 1. A process for producing dienes comprising: Silica (SiO 2 ) and alumina (Al 2 O 3 dehydrating at least one alkenol in the presence of at least one catalytic material comprising at least one acid catalyst based on The alumina content of the catalyst (Al 2 O 3 % based on the total weight of the catalyst (the alumina content refers to the total weight of the catalyst without binder), and the pore mode diameter is between 100 nm and 120 nm.

2. 2. The process of claim 1, wherein the alkenol is selected from 3-buten-2-ol (methyl vinyl carbinol), 3-buten-1-ol (allyl carbinol), 2-buten-1-ol (crotyl alcohol) or mixtures thereof.

3. 3. The process according to claim 1 or 2, wherein the alkenol is obtained directly from a biosynthetic process or by a catalytic dehydration process of at least one diol.

4. 2. The process of claim 1 , wherein the alkenol is derived from the catalytic dehydration of at least one diol.

5. 5. The process of claim 4, wherein the diol is bio-1,3-butanediol derived from fermentation of sugars derived from biomass.

6. The process according to claim 1, wherein the silica (SiO 2 ) and alumina (Al 2 O 3 ), wherein the acid catalyst based on aluminum alkoxide, soluble aluminum salt, aluminate is obtained by incipient wetness impregnation, the volume of the solution containing at least one alumina precursor selected from aluminum alkoxide, soluble aluminum salt, aluminate in an appropriate concentration is comparable to or slightly smaller than the pore volume of the solid support.

7. The process according to any one of claims 1 to 5, further comprising the step of: 2 ) and alumina (Al 2 O 3 The catalytic material comprises at least one acid catalyst based on Alumina (Al 2 O 3 or at least one of its precursors selected from aluminum alkoxides, soluble aluminum salts, aluminates; Alumina (Al 2 O 3 ) or at least one precursor thereof, 2 or an aqueous solution or suspension of at least one of its precursors selected from silicic acid, alkali metal silicates; The solid obtained by precipitation or gelation is collected and optionally subjected to subjecting the surface of the solid obtained to an ion exchange step with at least one compound capable of ion exchange, selected from aqueous solutions of salts containing ammonium ions; and / or At least one silica precursor selected from colloidal silica and silica alkoxide (SiO 2 ), or at least one alumina precursor selected from boehmite or pseudoboehmite (Al 2 O 3 and / or subjecting the mixture to a molding process such as extrusion, spheronization, tableting, or granulation; subjecting it to an optional heat treatment and / or an optional calcination, carried out before or after any of the aforementioned steps, i.e. ion exchange and / or bonding and / or shaping, and The process, wherein the pore mode diameter of the catalytic material comprising at least one acid catalyst based on silica (SiO 2 ) and alumina (Al 2 O 3 ) obtained after bonding and / or shaping is between 100 nm and 120 nm.

8. Silica (SiO 2 ) and alumina (Al 2 O 3 The specific surface area of ​​the acid catalyst based on 2 / g~800m 2 The process according to any one of claims 1 to 5, wherein the molar ratio is 1:1 / g.

9. The catalyst material is silica (SiO 2 ) and alumina (Al 2 O 3 At least one acid catalyst based on alumina (Al 2 O 3 ), silica (SiO 2 ), and at least one binder selected from zirconium oxide and titanium oxide.

10. Silica (SiO 2 ) and alumina (Al 2 O 3 At least one acid catalyst based on alumina (Al 2 O 3 ) or silica (SiO 2 and / or the catalyst material subjected to molding comprises at least one binder selected from the group consisting of 25 m 2 / g to 700m 2 10. The process of claim 9, wherein the specific surface area is 0.1-0.25 μm / g.

11. The process of claim 1, wherein the process for producing dienes is carried out using a diluent selected from an inert gas; or a compound having a boiling point of 50° C. or higher and a melting point of 40° C. or lower.

12. The process according to any one of claims 1 to 11, wherein the process for producing dienes comprises: When the diluent is selected from an inert gas, a molar ratio of diluent to alkenol of greater than 0.3 is used. When the diluent is selected from compounds having a boiling point of 50° C. or more and a melting point of 40° C. or less, a molar ratio of diluent to alkenol of 0.01 to 100 is used. The process that is carried out.

13. The process according to any one of claims 1 to 12, wherein the process for producing dienes comprises: At a temperature between 150°C and 500°C; and / or at a pressure between 0.05 bara and 50 bara (bara = absolute bar); and / or By manipulating the contact time (τ), calculated as the ratio of the loaded catalyst material to the feed volume, from 0.01 seconds to 10 seconds, The process that is carried out.

14. The process according to any one of claims 1 to 13, wherein the silica (SiO 2 ) and alumina (Al 2 O 3 wherein the catalytic material comprising at least one acid catalyst based on 1,2,4-tetramethylphenylacetamide is pretreated at a temperature at which the process for producing dienes is carried out.

Citation Information

Patent Citations

  • Method for producing conjugated diene compound and dehydration catalyst for allyl type unsaturated alcohol

    JP2016094402A

  • Method for producing conjugated diene compound by dehydration of allyl-type unsaturated alcohol

    JP2017197458A

  • Method for producing conjugated diene compound and dehydration catalyst of allyl-type unsaturated alcohol

    JP2017197459A

  • Method for producing dienes

    JP2018513111A